Spectral Element Numerical Investigation of Flow between Three Cylinders in an Equilateral-Triangular Arrangement with Different Spacing Distances - Zhenzhong Bao; Guoliang Qin; Wenqiang He; Yazhou Wang (Shock and Vibration)
Two-dimensional incompressible Navier-Stokes equations are numerically solved using the high resolution spectral element method at Reynolds number 200. The flow between three cylinders in an equilateral-triangular arrangement is investigated. The center-to-center spacing distance ratio between two circular cylinders is varied from 1.5 to 12. Present numerical results show that the flow patterns and force characteristics are the result of the combined effects of Reynolds number, spacing distance, configuration arrangement, and incident angle. For the small spacing distance ratio of 1.5, the well-known biased flow phenomenon in the gap of downstream cylinders is found. And the biased flow is bistable in our study but not monostable. A small spacing distance means lower Strouhal number, drag, and root-mean-square lift coefficients. In the medium spacing distance ratio of 4.0, the suppressed effect of vortex shedding for the presence of the side-by-side downstream cylinders disappeared. Mean drag coefficients of downstream cylinders are basically identical to the value of flow past around a single circular cylinder. For the large spacing distance ratio of 8.0, the effects between three cylinders basically disappeared. The mean drag and lift coefficients, root-mean-square lift coefficients, and Strouhal number of three cylinders are essentially equivalent to those values of a single circular cylinder.